(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper provides you comparative study of all the SDLC models and other hybrid methodologies of software development. This paper provide you all the advantages and disadvantages of the existing model and their limitation and also describe best uses of these models according to the situation. We described both contemporary models and traditional models which includes Sprial Model, Incremental Model, Spiral Model and V-Shaped Models are traditional models and Rapid Application Development Model, Agile software development comes under the contemporary models category.